2012
DOI: 10.18697/ajfand.50.11710
|View full text |Cite
|
Sign up to set email alerts
|

Child malnutrition and mortality in Swaziland: Situation analaysis of the immediate, underlying and basic causes

Abstract: Malnutrition is a major confounding factor for child morbidity and mortality in developing countries. In Swaziland, about 31% of the under-five children are stunted in growth, where-as 1% and 6% are wasted and underweight, respectively. Hhohho region has the highest prevalence of underweight children (8.2%) relative to other regions such as Shiselweni (7.3%), Lubombo (6.7%) and Manzini (6.4%). The prevalence of infant and under-five children mortality rate (per 1,000 live births) are 85 and 102 deaths, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…There is a need to educate the members of the public on sustainable techniques for home and school gardening, crop harvesting, preservation, and processing methods to limit post-harvest losses and retain the vital nutrients in the foods consumed. Home or school gardening is very important because it produces nutritious food and also assists in terms of food security (Masuku-Maseko & Owaga, 2012).…”
Section: Results and Discussion The Underlying Causes Of Malnutrition...mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a need to educate the members of the public on sustainable techniques for home and school gardening, crop harvesting, preservation, and processing methods to limit post-harvest losses and retain the vital nutrients in the foods consumed. Home or school gardening is very important because it produces nutritious food and also assists in terms of food security (Masuku-Maseko & Owaga, 2012).…”
Section: Results and Discussion The Underlying Causes Of Malnutrition...mentioning
confidence: 99%
“…When children and older people are sick they can easily become malnourished because of loss of appetite and increased nutritional requirements. Moreover, these people will need proper health care and the majority of the members of the communities in rural areas rely on public health for treatment (Masuku-Maseko & Owaga, 2012). Proper health care refers to one being able to access treatment and prevention of diseases.…”
Section: Poor Health Services and An Unhealthy Household Environmentmentioning
confidence: 99%
“…Jenis Makanan Pendamping ASI yang tepat harus diberikan sesuai dengan tahapan usia anak (Menteri Kesehatan RI, 2014). Pemberian MP-ASI terlalu dini atau terlalu lama serta kurang tepatnya porsi dan frekuensi pemberianan makanan dapat menyebabkan masalah gizi (Maseko & Owaga, 2012). Oleh karena itu, penyataan Andriani et al, (2022) menyatakan bahwa edukasi MP-ASI dianggap lebih efektif untuk meningkatkan pengetahuan Ibu sehingga kedepannya permasalahan gizi bisa terhindarkan.…”
Section: A Latar Belakangunclassified
“…2 This translates to a number of children born in Eswatini dying before reaching their fifth birthday and malnutrition is said to be one of the causes of this high mortality. 10 …”
Section: Introductionmentioning
confidence: 99%
“…2 This translates to a number of children born in Eswatini dying before reaching their fifth birthday and malnutrition is said to be one of the causes of this high mortality. 10 The Cost of Hunger Report indicated that every year, Eswatini has lost an estimated $92 million as a result of child under-nutrition, which is equivalent to 3.1% of the gross domestic product (GDP), a loss that will recur annually if chronic malnutrition prevalence is not addressed and decreased. 11 There have been a number of studies conducted focusing only on the prevalence of several health conditions in the country, including malnutrition.…”
Section: Introductionmentioning
confidence: 99%